The Temporal Version of the Pediatric Sepsis Biomarker Risk Model - Wong, Hector R.; Weiss, Scott L.; Giuliano, John S.; Wainwright, Mark S.; Cvijanovich, Natalie Z.; Thomas, Neal J.; Allen, Geoffrey L.; Anas, Nick; Bigham, Michael T.; Hall, Mark; Freishtat, Robert J.; Sen, Anita; et al. (PLoS ONE, 2014)
PERSEVERE is a risk model for estimating mortality probability in pediatric septic shock, using five biomarkers measured within 24 hours of clinical presentation. Here, we derive and test a temporal version of PERSEVERE (tPERSEVERE) that considers biomarker values at the first and third day following presentation to estimate the probability of a "complicated course", defined as persistence of ≥2 organ failures at seven days after meeting criteria for septic shock, or death within 28 days. Biomarkers were measured in the derivation cohort (n = 225) using serum samples obtained during days 1 and 3 of septic shock. Classification and Regression Tree (CART) analysis was used to derive a model to estimate the risk of a complicated course. The derived model was validated in the test cohort (n = 74), and subsequently updated using the combined derivation and test cohorts. A complicated course occurred in 23% of the derivation cohort subjects. The derived model had a sensitivity for a complicated course of 90% (95% CI 78-96), specificity was 70% (62-77), positive predictive value was 47% (37-58), and negative predictive value was 96% (91-99). The area under the receiver operating characteristic curve was 0.85 (0.79-0.90). Similar test characteristics were observed in the test cohort. The updated model had a sensitivity of 91% (81-96), a specificity of 70% (64-76), a positive predictive value of 47% (39-56), and a negative predictive value of 96% (92-99). tPERSEVERE reasonably estimates the probability of a complicated course in children with septic shock. tPERSEVERE could potentially serve as an adjunct to physiological assessments for monitoring how risk for poor outcomes changes during early interventions in pediatric septic shock.